The Republic of Macedonia in the process of accession to the European Union - Donev, Dejan (Odsek za medijske studije, Filozofski fakultet, Novi Sad, 2013)
Since independence in 1991, Republic of Macedonia is attempting to become part of the family where it belongs geographically. It is so because R. Macedonia is surrounded by neighbors with whom the country shares the history, the reality and the European future. Hence, the desire to join the European Union comes from the idea to always be a constructive and relevant part of the big family.
Република Македонија во процесот на придружување кон Европската Унија